Evolutionary Stability of Salmonella Competition with the Gut Microbiota: How the Environment Fosters Heterogeneity in Exploitative and Interference Competition. Issue 23 (22nd November 2019) - Müller, Johannes; Spriewald, Stefanie; Stecher, Bärbel; Stadler, Eva; Fuchs, Thilo M.
Abstract: Following ingestion, gastrointestinal pathogens compete against the gastrointestinal microbiota and overcome host immune defenses in order to cause infections. Besides employing direct killing mechanisms, the commensal microbiota occupies metabolic niches to outcompete invading pathogens. Salmonella enterica serovar Typhimurium ( S. Typhimurium) uses several strategies to successfully colonize the gut and establish infection, of which an increasing number is based on phenotypic heterogeneity within the S. Typhimurium population. The utilization of myo -inositol (MI) and the production of colicin confer a selective advantage over the microbiota in terms of exploitative and interference competition, respectively. In this review, we summarize the genetic basis underlying bistability of MI catabolism and colicin production. As demonstrated by single-cell analyses, a stochastic switch in the expression of the genes responsible for colicin production and MI degradation constitutes the heterogeneity of the two phenotypes. Both genetic systems are tightly regulated to avoid their expression under non-appropriate conditions and possible detrimental effects on bacterial fitness. Moreover, evolutionary mechanisms underlying formation and stability of these phenotypes in S. Typhimurium are discussed. We propose that both MI catabolism and colicin production create a bet-hedging strategy, which provides an adaptive benefit for S. Typhimurium in the fluctuating environment of the mammalian gut. Highlights: Phenotypic heterogeneity, e.g. the emergence of isogenic subpopulations with different behavior, is a fitness enhancer of bacteria. Salmonella enterica possesses several specific capacities based on heterogeneity, among them the production of colicin and the utilization of myo-inositol (MI). Both allow this enteropathogen to successfully compete with residing gut microbiota during infection. Several mechanisms could be identified that underlie the stochastic bistability of gene expression in colicin production and MI catabolism, thus evolutionary selecting for these heterogeneous phenotypes in Salmonella. We hypothesize that the fluctuations of gene expression in the two examples result in a bet-hedging strategy and provide an adaptive benefit for S. enterica in vivo under switching environments. Graphical Abstract: Unlabelled Image